The concept of happiness in transhumanism and realistic bioethics - Haros Becerra, Lourdes Celene (2023)
Considering one of the most outstanding bioethical approaches about transhumanism, this shows that is directly related to the human being's happiness and plenitude; since all its proposals aspire to provide a solution, by means of development and application of Emerging Technologies to all the origins of the pain, suffering and life length that a human being could experience. Hence, this article proposes to expose a critical analysis of the concept of happiness in transhumanism and realistic bioethics. Some of the most outstanding authors or promoters representing transhumanism and other authors in accordance with realistic bioethics have been considered for the presentation of this research.